Thinking about addiction : hyperbolic discounting and responsible agency - Hanson, Craig (Value inquiry book series, 2009)
What is addiction? Why do some people become addicted while others do not? Is the addict rational? In this book, Craig Hanson attempts to answer these questions and more. Using insights from the beginnings of philosophy to contemporary behavioral economics, Hanson attempts to assess the variety of ways in which we can and cannot, understand addiction. Special consideration is given to a challenging (and controversial) proposal dubbed "hyperbolic discounting." Hanson proposes some modifications to the hyperbolic discounting view that permit it to explain not only addiction, but also a variety o.